FORMULATION AND IN VITROEVALUATION OF GLIPIZIDE MUCOADHESIVE BUCCAL TABLETS - SELLAPPAN VELMURUGAN; KIRAN KUMAR.RAGHAVARAPU (International Journal of Pharma and Bio Sciences, 2013)
The aim of study was to prepare and characterize mucoadhesive buccal tablets of glipizide using different Mucoadhesive polymers such as Carbopol 940, Sodium alginate and HPMC K15M in combination. Twenty one formulation were developed with different concentration of mucoadhesive polymers in each formulation.The formulated buccal tablets were tested for surface pH,in vitro drug release and moisture absorption. The prepared tablets also evaluated for bioadhesive strength, exâ€vivo residence time and drug permeation through porcine buccal mucosa. In vitro bioadhesive strength, exâ€vivo residence time and in vitro release studies showed that formulation F5 containing 1:8 ratio of drug and polymer combination showed satisfactory bioadhesive and exhibited optimum drug release (72.35±0.04 after 12hrs). DSC results showed no evidence of strong interaction between the drug and polymers. The results indicated that suitable bioadhesive buccal tablets with desired permeability could be prepared. Stability of glipizide mucoadhesive buccal tablets was determined in natural human saliva; it was found that both glipizide and buccal tablets were stable in human saliva.